Emerging East Asia sukuk market: human development and growth indicators - Ahmad, Nursilah; Duasa, Jarita (USIM Press, Universiti Sains Islam Malaysia, 2019)
Emerging East Asia’s sukuk market comprises Brunei, China, Indonesia, Malaysia and Singapore. These markets were affected by the falling oil prices, slow global growth, anticipated rise hikes by the United States Federal Reserve. Growth are sustained by acceptance of sukuk as financing demand and interst from nonmainstream sukuk markets. Malaysia dominates the regional market followed by Indonesia. Even though the sukuk market slow down in 2015, it started to pick-up in 2019 resulting from expansionary budget, infrastructure financing and and refinancing needs arising from maturing debt. Due to potential growing market share, it is also important to evaluate these economies from human development perspective comprises of growth, social, health and environmental indicators. Using Japan and Singapore as the benchmark country, the analysis suggest that most countries are most likely to converge to Japan. Therefore, Japanese economic policies could be the barometer for Emerging East Asia sukuk market.